STUDI DESKRIPTIF PENGUNJUNG POSBINDU PTM DI DUA RUKUN WARGA KELURAHAN PEJAGALAN - Yunisa Astiarani; Kevin Kristian (Atma Jaya Catholic University of Indonesia, 2019)
Introduction: A community-based health post called ‘pos pembinaan terpadu’ (Posbindu) is a vital approach to NCDs prevention and control strategy in the community. However, the posts appear to receive low appreciation in urban areas, with less than 10% of the population at risk visiting the post. This study presented a descriptive evaluation in Posbindu visitors after half-year implementation in two hamlets in Pejagalan. Methods: A survey-based study was conducted in two Posbindu, each in a hamlet. A self-questionnaire regarding sociodemography, NCDs status, risk factors, visiting frequency and health-seeking behaviour were asked to all visitors and collected during Posbindu schedule. Results: Posbindu visitors in hamlet A and B (131 and 160) share common demographic characteristics, with women participation higher in both (Hamlet A= 90.1% and Hamlet B=80.6%) mostly in their 30-44 age group for hamlet A (38.9%) and 45-59 age group for hamlet B (50%). Homemakers and unemployed were more than 70% of the proportion with low education preceding (40%) in both hamlets. NCDs status slightly higher in hamlet A (54.1%) than in B (53.7%), with hypertension, occupied the most. More than 90% of visitors lack in physical activity. Health seeking behaviour is better in diabetes sufferer than hypertension. Conclusion: Posbindu visitors are usually housewives or unemployed group due to limitation of schedule. School and workplace-based NCDs prevention program have to be in consideration. Open space facilities on increasing the community's physical activity and intensive health literacy are necessary to maintain their healthy life years.